Supporting multi-agent systems life cycle by integrating Protege and Prometheus. (12th July 2010) - Sokolova, Marina V.; Fernandez-Caballero, Antonio
In this paper, an approach aiming to support the complete multi-agent systems (MAS) life cycle is proposed. Two existing and widely accepted tools, Protege Ontology Editor and Knowledge-Base Framework and Prometheus Development Kit, are integrated, offering a general sequence of steps facilitating application creation. It seems reasonable to integrate all traditional software development stages into one single methodology, which can provide a general approach for MAS creation, starting with problem definition and resulting in program coding, deployment and maintenance. The approach is successfully being applied to situation assessment issues, which has concluded in an agent-based decision-support system for environmental impact evaluation. An example is offered to evaluate the impact of environmental parameters upon human health in Spanish region Castilla-La Mancha, in general, and in the city of Albacete, in particular.